Confessionalidade na escola: a relação entre religião e educação no projeto educativo da Rede Marista - Borba, Fernanda Matos de (2014)
Confessionality in the school is the theme of this paper which intends to present research with regard to the relation between religion and education in the educational Project of the Marist Basic Education Network, unveiling influences and evidences of how the Catholic confessionality is characterized and permeates the educational project of the Colégio Marista Pio XII, one of the educational units of the Marist Network, situated in Novo Hamburgo, Rio Grande do Sul. To carry out this study a documental bibliographic research was carried out about the themes developed in order to understand the issue and analyze the content, according to Laurence Bardin, as a resource for the construction of categories for qualitative analysis. In the research of the Marist documents three categories of analysis were listed: confessional school, school in ministry and a Marist school. Divided into two chapters, this thesis initially deals with relevant concepts and aspects in the comprehension of the relation between religion and education in the school, such as religious identity, confessionality and religious plurality, confessional education, religious education, the issue of the foundational charisma in Catholic schools, their insertion in society and their contribution to the ethics perspective. In the second part one finds a brief explanation about the Catholic confessional school and the analysis of the Maris documents, according to the goals of the research. Based on this study, the conclusion is that the Colégio Marista Pio XII manifests its Catholic and Marist confessionality through its documents, it is in consonance with the Catholic Church and is very clear about its missionary and educational role in society.